The Relationship between Perfectionism and Students’ Academic burnout - Rahma Nanda, Julika Mutiara; Sugiyo, Sugiyo; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2022)
Academic burnout is a common problem experienced by students. Thus, this study attempted to identify and analyze the relationship between perfectionism and academic burnout by involving public senior high school students throughout Sungai Lilin sub-district amounted to 300 people chosen using cluster random sampling. Their data were collected using the instruments of Maslach Burnout Inventory-Students Survey (MBI-SS) and Frost Multidimensional Perfectionism Scale (FMPS) modified into Indonesian which gained alpha coefficient of 0.84 and 0.97 respectively. Findings indicated that four of six aspects of maladaptive perfectionism, concern over mistakes, parental expectation, and parental criticism positively correlated with academic burnout, while the aspect of doubt about actions had a negatively correlation. In addition, two adaptive perfectionism aspects, namely personal standards and organizations had no correlation with academic burnout. These imply that students need to be enlightened about awareness of the impact of maladaptive perfectionism and adjusted to the adaptive ones so that their burnout can be solved.